Understanding sustainable development - Blewitt, John, 1957- (Routledge, 2015)
"This new and expanded edition builds upon the first edition's powerful multi-perspective approach and breath of coverage. A truly comprehensive introduction to sustainable development, it is designed specifically to allow access to the topic from a wide range of educational and professional backgrounds and to develop understanding of a diversity of approaches and traditions at different levels.This second edition includes:a complete update of the text, with increased coverage of major topics including ecosystems; production and consumption; business; urban sustainability; governance; new media technologies; conservation; leadership; globalization and global crises; sustainability literacy and learning;more examples from the Global South and North America, while retaining its unique coverage of first world countries;chapter aims at the start and summaries at the end of each chapter; glossary of key terms; a new chapter on Conservation with a focus on behaviour change and values;a brand new website which includes discussion of how projects are done on the ground, additional exercises and online cases, test questions and recommended readings and films.Offering boxed examples from the local to the global, Understanding Sustainable Development is the most complete guide to the subject for course leaders, undergraduates and postgraduates"--Resumé vydavatele